The process of pain assessment in people with dementia living in nursing homes: a scoping review - Caroline Kreppen Overen; Maria Larsson; Adelheid Hummelvoll Hillestad; Ingela Karlsson; Siren Eriksen (Palliative Care and Social Practice)
Background: Pain is a common symptom in people with dementia living in nursing homes, but cognitive impairment, including language and communication difficulties, challenges pain assessment and the ability to self-report pain. Objectives: This study aimed to identify and summarize patterns, advances, and gaps in research literature describing pain assessment in people with dementia living in nursing homes. Design: We conducted a scoping review following Arksey and O’Malley’s methodological framework. Methods: Systematic searches were conducted in CINAHL, Embase, MEDLINE, and PsycINFO. We included studies describing pain expressions in people with dementia and/or healthcare personnel assessment of pain in people with dementia, in a nursing home context. Charted data included demographics, methodological descriptions, ethical and quality assessment and relevant findings. Relevant findings were summarized using thematic analysis, and an overview of patterns, advances, and gaps in the research literature is presented. Results: Thirty-nine studies were included. The results describe three patterns: (1) pain awareness; (2) suspected pain and (3) pain mapping. Collectively, these patterns constitute a process of pain assessment, integrating pain expressions of people with dementia. Important perspectives on self-reporting are touched upon in several of the included studies, though direct descriptions of attempts to capture the residents’ own experience of pain are sparse. Conclusion: This scoping review provides a comprehensive description of pain assessment in people with dementia living in nursing homes as a process in three steps. We identified several knowledge gaps in the understanding of this process and provide concrete recommendations for further research. The results underpin the importance of pain assessment approaches that incorporate the flexibility to meet residents’ varying and potentially fluctuating ways of communicating pain. Trial registration: This scoping review is registered in the Open Science Framework ( https://osf.io/8kaf5/ ).